Penerapan Teknik Single Linkage Dalam Klasterisasi Mahasiswa Berdasarkan Indikator Pembidangan Skripsi - Silalahi, Eci Marcelina; Bu'ulolo, Efori (Building of Informatics, Technology and Science (BITS), 2021)
Pelita Nusantara Medan STMIK Computer Informatics study program provides several fields of science that students can choose in completing their final thesis in the form of a thesis. During this time in its implementation, the determination of the field of this thesis was chosen by the student who will submit the thesis title as one of the requirements to obtain a bachelor's degree at STMIK Pelita Nusantara Medan without any direction from the campus either from the academic department or the head of the study program. Therefore, not a few students who ultimately choose a field of science that is not in accordance with their abilities. Based on the existing problems regarding the development of this thesis, a student clustering system was made based on the indicators of thesis development by applying one of the data mining methods, namely clustering, where the technique used was the Single Linkage Technique. Single Linkage Technique is a way to group objects or individuals based on criteria similarity size or closest distance between objects (minimum distances). Thus, the results of clustering (clustering) that are designed can help the academic STMIK Pelita Nusantara Medan, especially the Chairperson of the Computer Informatics Study Program in directing students in the determination of the field of thesis so that students choose the field of thesis in accordance with their abilities